A prototype regional stock-flow consistent model - Francesco Zezza; Gennaro Zezza (Levy Economics Institute of Bard College, 2022)
Starting from the seminal works of Wynne Godley (1999; Godley and Lavoie 2005, 2007a, 2007b), the literature adopting stock-flow consistent (SFC) models for two or more countries has been flourishing, showing that consistently taking into account real and financial markets of two open economies will generate different results with respect to more traditional open economy models. However, few contributions, if any, have modeled two regions in the same country, and our paper aims at filling this gap. When considering a regional context, most of the adjustment mechanisms at work in open economy models-such as exchange rate movements, or changes in interest on public debt-are simply not present, as they are controlled by "external" authorities. So, what are the adjustment mechanisms at work? To answer this question, we adapt the framework suggested in Godley and Lavoie (2007a) to consider two regions that share the same monetary, fiscal, and exchange rate policies. We loosely calibrate our model to Italian data, where the South (Mezzogiorno) has both a lower level of real income per capita and a lower growth rate than the North. We also introduce a fragmented labor market, as discouraged workers in the South will move North in hopes of finding commuting jobs. Our model replicates some key features of the Italian economy and sheds light on the interactions between financial and real markets in regional economies with "current account" imbalances.
Keywords: E12; J61; R12; 330; Stock-Flow Consistent; Regional Labor Mobility; Regional Economic Activity and Development